112k views
4 votes
Which expression is equivalent to the following complex fraction? -2/x+5/y/3/y-2/x​

2 Answers

6 votes

Answer:


(5x -2y)/(3x - 2y)

Explanation:

I think you mean this:


((-2)/(x)+(5)/(y))/((3)/(y)-(2)/(x)​)=


= ((-2y)/(xy) + (5x)/(xy))/((3x)/(xy) - (2y)/(xy)​)


= ((5x -2y)/(xy))/((3x - 2y)/(xy)​)


= (5x -2y)/(xy) * (xy)/(3x - 2y)


= (5x -2y)/(3x - 2y)

User Bijay Yadav
by
5.0k points
3 votes

Answer:

it's A

Explanation:

User Manoj
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.